หอสมุดรัฐสภาและหอสมุดแห่งชาติของสหรัฐอเมริกา - บุรีรักข์ นามวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
The historical background and the general information of the Library of Congress have been reviewed since its first establishment in 1800. Notes that the Library of Congress is in all probability the world’s largest library, created for and by the Congress. Its usefulness is extended not only to the Congress but also to, through various services, other Government Agencies, other libraries throughout the country and the world, and to the general public. Organization and administration of the Library of Congress are presented in the following sections: Office of the Library, Administrative Department, Reference Department, Copyright Office, Law Library, and the Congressional Research Service (CRS). Describes various types of services provided for the Congress by the CRS.